Dynamic visual cryptography based on chaotic oscillations - Petrauskiene, Vilma; Palivonaite, Rita; Aleksa, Algiment; Ragulskis, Minvydas (Communications in nonlinear science & numerical simulation, 2014)
•A dynamic visual cryptography scheme based on chaotics oscillations is developed in this paper.•The secret image is leaked when the cover image is oscillated by a chaotic law.•The relationship among the standard deviation, the pitch of the grating and the pixel size is derived. Dynamic visual cryptography scheme based on chaotic oscillations is proposed in this paper. Special computational algorithms are required for hiding the secret image in the cover moiré grating, but the decryption of the secret is completely visual. The secret image is leaked in the form of time-averaged geometric moiré fringes when the cover image is oscillated by a chaotic law. The relationship among the standard deviation of the stochastic time variable, the pitch of the moiré grating and the pixel size ensuring visual decryption of the secret is derived. The parameters of these chaotic oscillations must be carefully preselected before the secret image is leaked from the cover image. Several computational experiments are used to illustrate the functionality and the applicability of the proposed image hiding technique.